1979
DOI: 10.1159/000466927
|View full text |Cite
|
Sign up to set email alerts
|

Probable Biosynthetic Pathway for the Synthesis of the B Antigen from B(h) Variants

Abstract: Red cells and serum from two B(h) variants (B+H-cells) have been investigated for B and H blood group glycosyltransferases. The H enzyme could not be detected using either type 1 or type 2 chain acceptors. The B enzyme was present in normal amount when 2'-fucosyllactose was used as substrate, neither 6'-fucosyllactose nor 6'-fucosyllactosamine could act as acceptors for the B enzyme. Upon treatment of the B(h) red cells by the B-degrading enzyme from Trichomonas foetus the B antigen was destroyed while H deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…[438] demonstrated that H is the precursor of B on the cells of a B h individual. Consequently, the small amount of H produced is completely converted to A or B. Mulet et al .…”
Section: H Mmentioning
confidence: 99%
“…[438] demonstrated that H is the precursor of B on the cells of a B h individual. Consequently, the small amount of H produced is completely converted to A or B. Mulet et al .…”
Section: H Mmentioning
confidence: 99%
“…od->3/4 and ctl-~2 fucosidase were purified from an ultrasonic extract of Trichomonas foetus by fractionation on Sepharose 4B followed by chromatography on DEAE-cellulose [13], the enzymes being eluted with 0.7 M and 0.15 M KC1, respectively.…”
Section: Enzymesmentioning
confidence: 99%